An Analysis of the Experiences of Developed Countries in Conducting Monitoring Studies of Carrier Trajectories of Graduates from Institutions of Vocational (Technical and Vocational) Education and Its Adaptation for Ukraine - Liesnikova М. V. (Statistics of Ukraine, 2024)
Vocational (Technical and Vocational) education (V(TV)E), being a crucial sector for the labor market, is supposed to take effective steps aimed at the recovery and strengthening of the Ukrainian economy. These steps include conducting monitoring studies of graduates from V(TV)E institutions. Clarity about the situation with the graduates’ integration in the labor market, being a key source for the assessment of a relevance of their diplomas to the needs of regional labor markets, is of vital important for the Ukrainian V(TV)E system. The article’s objective is to explore advanced practices of monitoring studies of graduates from V(TV)E institutions, with emphasis on EU countries, and a feasibility of their adaptation for Ukraine. An analysis of EU countries showed that each of them was conducting monitoring studies of graduates from V(TV)E institutions on well-established, regular or irregular basis. Data from administrative registers and interviews are used to produce quantitative and qualitative estimates characterizing the results of training and obtained qualification, training duration, satisfaction with the obtained diploma, graduate’s job placement and promotion in the labor market, job seeking duration, type of contract, amount of salary, utilizing the skills acquired in time of training on the job place, etc. The produced data are used in taking administrative decisions on improving operative schemes of the V(TV)E system. Ukraine has been taking steps towards the implementation of monitoring studies of graduates from V(TV)E institutions. Thus, the expert group of EU4SKILLS program “Better skills for modern Ukraine” conducted a pilot monitoring interview of graduates from V(TV)E institutions in 2020. Its results showed that using the graduates’ skills acquired in time of training on a regional labor market can be an indicator of this market performance. A monitoring study of the carrier trajectory of graduates from V(TV)E institutions was conducted in Ukraine in 2023, for purposes of analysis of their life plans, carrier trajectories and specifics of the job placement process in the conditions of martial law and postwar recovery of Ukraine. The implementation of monitoring studies of graduates from V(TV)E institutions in Ukraine will be promoted by creating the V(TV)E module in the software and hardware complex “Computerized complex of educational management”, integrated with the web-program LimeSurvey and containing administrative data of the graduates. The subject for further research is development of methodical recommendations for monitoring studies of carrier trajectories of graduates from V(TV)E institutions.